Relativity and structure deformations: epistemological aspects - Lambert, Dominique (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
In contemporary philosophy of science there is a long lasting discussion concerning the evolution of physical theories. One analyzes the so-called limiting transitions from new theories to older ones (the correspondence principle). The present author notices that contemporary science has at its disposal a technical tool with the help of which the inverse process can be analyzed, namely a deformation of an older theory to the newer (more general) one. The author briefly presents the mathematical theory of structure deformations and discusses its applications to philosophy of science. For instance, with help of this theory the concepts of commensurability or non-commensurability of physical theories can be precisely defined. The chain of structure deformations is described in changing from classical mechanics to special relativity and then to general relativity, and from classical mechanics to quantum mechanics. Some consequences of this approach for the search of quantum gravity are also outlined. In spite of the great epistemological significance of the theory of structure deformations, the role of human inventiveness in scientific creativity remains irreplaceable.